2001
DOI: 10.1081/ese-100106248
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Iodinated X-Ray Contrast Media in Domestic Effluents and Their Fate During Indirect Potable Reuse

Abstract: This study investigated the occurrence of pharmaceuticals, emphasizing triiodinated benzene derivatives used as X-ray contrast media, in domestic effluents and their fate during subsequent groundwater recharge. Organic iodine measurements were used as a surrogate for triiodinated benzene derivatives. Seven wastewater treatment facilities in Texas, Arizona and California were studied and organic iodine concentrations at these facilities varied between 5 and 40 microg iodine/L. The highest concentrations were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 10 publications
3
42
0
Order By: Relevance
“…However, a large number of recent studies have demonstrated persistence of these pharmaceuticals in the aquatic environment. The occurrence of several pharmaceutical compounds have been reported in sewage treatment plant effluents as well as in surface waters in Germany (Ternes, 1998;Hirsch et al, 1999;Putschew et al, 2000), the Netherlands (Belfroid et al, 1999), Switzerland (Soulet et al, 2002), Canada Miao et al, 2004), Brazil , Italy (Castiglioni et al, 2004), Spain (Rodrı´guez et al, 2003), and the United States (Drewes et al, 2001; Kolpin et al, 2002). The detected compounds included antibiotics, anticonvulsants, painkillers, cytostatic drugs, hormones, lipid regulators, beta-blockers, antihistamines, and X-ray contrast media.…”
Section: Occurrence and Fate Of Pharmaceuticals In The Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a large number of recent studies have demonstrated persistence of these pharmaceuticals in the aquatic environment. The occurrence of several pharmaceutical compounds have been reported in sewage treatment plant effluents as well as in surface waters in Germany (Ternes, 1998;Hirsch et al, 1999;Putschew et al, 2000), the Netherlands (Belfroid et al, 1999), Switzerland (Soulet et al, 2002), Canada Miao et al, 2004), Brazil , Italy (Castiglioni et al, 2004), Spain (Rodrı´guez et al, 2003), and the United States (Drewes et al, 2001; Kolpin et al, 2002). The detected compounds included antibiotics, anticonvulsants, painkillers, cytostatic drugs, hormones, lipid regulators, beta-blockers, antihistamines, and X-ray contrast media.…”
Section: Occurrence and Fate Of Pharmaceuticals In The Environmentmentioning
confidence: 99%
“…In addition, the removal of triiodinated X-ray contrast media by sorption is poor due to their high hydrophilicity. These contrast agents are excreted with no marked metabolic transformation and contribute to the increase of absorbable organic halogens (AOX) in hospital wastewater (Gartiser et al, 1996), as well as high concentration of absorbable organic iodine (AOI) in sewage treatment plant effluent (5 to 40 mg I/L) (Drewes et al, 2001), surface water and raw drinking water (11 to 13 mg I/L) (Putschew et al, 2000). Although it has been suggested that no environmental risk is evident based on a battery of acute and chronic toxicity test data of triiodinated X-ray contrast media (Steger-Hartmann et al, 1999), their relatively high environmental concentrations, persistence, mobility, as well as the lack of information regarding potential sub-lethal effects have generated interests in the application of advanced water and wastewater treatment processes including ozonation and AOPs.…”
Section: X-ray Contrast Mediamentioning
confidence: 99%
See 3 more Smart Citations